ARP-1 Regulates the Transcriptional Activity of the Aromatase Gene in the Mouse Brain - Honda, Shin-ichiro; Harada, Nobuhiro (Frontiers in Endocrinology, 2020)
An important function of aromatase in the brain is conversion of testosterone secreted from the testis into estradiol. Estradiol produced in the brain is thought to be deeply involved in the formation of sexually dimorphic nuclei and sexual behavior as a neurosteroid. We analyzed the brain-specific promoter to elucidate the control mechanisms of brain aromatase expression that may be highly involved in sexual differentiation of the brain. The 202 bp upstream region of the brain-specific exon 1 has three types of cis-acting elements, aro-AI, AII, and B. We isolated ARP-1 as an aro-AII binding protein by yeast one-hybrid screening from a cDNA library of mouse fetal brains. ARP-1 is a member of the nuclear receptor superfamily and functions as an orphan-type transcription factor. ARP-1 protein synthesized in vitro showed the same binding property to the aro-AII site as nuclear extract from fetal brains. To determine how the promoter is involved in brain-specific transcription of the aromatase gene, we first the detected the in vivo occupancy of the aro-AII site by ARP-1 using chromatin immunoprecipitation assays. Diencephalic regions of fetal brains at embryonic day 16 were analyzed, which revealed ARP-1 recruitment to the aro-AII site. To analyze the effects of ARP-1 on transcriptional regulation of the brain-specific aromatase promoter, a luciferase reporter plasmid driven by the brain-specific promoter was transfected into CV-1 cells together with a plasmid expressing ARP-1 protein. These analyses revealed that ARP-1 induced promoter activity in a dose-dependent manner. Furthermore, to determine whether ARP-1 is required for aromatase expression in neurons, ARP-1 knockdown was conducted in neuronal cell primary culture. Knockdown of ARP-1 significantly suppressed the increase in aromatase mRNA observed in cultured neurons. These results indicate that ARP-1 is involved in the transcriptional regulation of the brain-specific promoter of the aromatase gene.